Diversity of Stemphylium spp. of onion and garlic revealed the differential pathogenicity and in vitro efficacy of different growth suppressors - Md. Morshedul Islam; Sabmira Showkat Silvi; Shila Chakraborty; Md. Atiqur Rahman Khokon (Heliyon)
Stemphylium blight of onion and garlic, induced by Stemphylium vesicarium, is a serious concern in Bangladesh due to the devastation and economic loss. Twenty isolates of Stemphylium spp. From different locations were collected and their cultural, morphological, molecular, and pathological diversity were analyzed. Cultural variations were distinct having the maximum radial mycelial growth (43.00 mm) and the minimum (37.13 mm) at the end of colonization. Prominent diversity was also found in colony textures, elevations, shapes, and colors of the conidia. Molecular identification was done for precise recognition and delineation. The internal transcribed spacer (ITS) region was amplified using the universal primers ITS1 and ITS4 which provided an amplicon of 600 bp. Further, all PCR products were sequenced to find the homology with the GenBank accessions of NCBI. Different isolates showed 82.92–100.00 % similarity with S. vesicarium and S. lycopersici. The phylogeny of the Stemphylium isolates indicated the presence of two distinct species of Stemphylium where 18 isolates exhibited similarity with S. vesicarium and 2 isolates were associated with S. lycopersici. Isolate GNMM-42 (OR923573) had the highest virulence. Salicylic acid (SA), benzoic acid (BA), and chitosan (CHI) exhibited in vitro antifungal effects against S. vesicarium. However, chitosan @ 40 ppm exhibited the most significant growth inhibitory effect (98.78 %). The findings indicate that S. vesicarium was the predominant species that caused the Stemphylium blight in onion and garlic. A considerable variation exists in cultural, morphological, molecular, and pathological characteristics among the Stemphylium isolates. Additionally, SA, BA, and CHI showed growth suppressive effects and can be utilized as alternative compounds to toxic fungicides in the existing integrated disease management package in Bangladesh.